Biomass from landscape management of grassland used for biogas production: effects of harvest date and silage additives on feedstock quality and methane yield. (19th September 2013) - Herrmann, C.; Prochnow, A.; Heiermann, M.; Idler, C.
Abstract Biogas production from grassland biomass harvested during landscape management may help to maintain species‐rich grassland biotopes, but extensive management and late harvests often result in low‐quality biomass. Biogas production from the vegetation of Alopecuretum pratensis, Molinietum caeruleae and Caricetum gracilis, three typical grassland biotopes in north German nature reserves, was investigated in relation to harvest date. In addition, the A. pratensis vegetation was investigated for ensiling and the application of bacterial silage additives. Results indicate that biogas production might be a reasonable utilization pathway for grassland biomass from landscape management if the first cut occurs up to late summer. Methane yields of grassland biomass decreased substantially with later harvest, from up to 309 lN kg−1 organic dry matter (ODM) in May to below 60 lN kg−1 ODM in February, in correlation with increasing crude fibre contents. Caricetum gracilis vegetation was the least suitable feedstock for biogas production. It showed a rapid decline in methane yields with later harvest and 25% lower methane yields compared with other types of grassland vegetation. Application of silage additives is recommended for adequate preservation of grassland biomass from landscape management by ensiling. Addition of homofermentative lactic acid bacteria improved acidification during ensiling if sufficient fermentable sugar was available. The use of inoculant and molasses enhanced methane yields by 3–55%. Additional carbohydrate source is necessary to ensure proper ensilage when grasses are harvested after late autumn.